Nestin(+) Tissue-Resident Multipotent Stem Cells Contribute to Tumor Progression by Differentiating into Pericytes and Smooth Muscle Cells Resulting in Blood Vessel Remodeling - Klein, Diana; Meissner, Nicole; Kleff, Veronika; Jastrow, Holger; Yamaguchi, Masahiro; Ergün, Süleyman; Jendrossek, Verena (Frontiers in Oncology, 2014)
Tumor vessels with resistance to anti-angiogenic therapy are characterized by the normalization of the vascular structures through integration of mature pericytes and smooth muscle cells (SMC) into the vessel wall, a process termed vessel stabilization. Unfortunately, stabilization-associated vascular remodeling can result in reduced sensitivity to subsequent anti-angiogenic therapy. We show here that blockade of VEGF by bevacizumab induces stabilization of angiogenic tumor blood vessels in human tumor specimen by recruiting Nestin-positive cells, whereas mature vessels down-regulated Nestin-expression. Using xenograft tumors growing on bone-marrow (BM) chimera of C57Bl/6 wildtype and Nestin-GFP transgenic mice we show for first time that Nestin(+) cells inducing the maturation of tumor vessels do not originate from the BM but presumably reside within the adventitia of adult blood vessels. Complementary ex vivo experiments using explants of murine aortas revealed that Nestin(+) multipotent stem cells (MPSCs) are mobilized from their niche and differentiated into pericytes and SMC through the influence of tumor-cell secreted factors. We conclude that tissue-resident Nestin(+) cells are more relevant than BM-derived cells for vessel stabilization and therefore have to be considered in future strategies for anti-angiogenic therapy. The identification of proteins mediating recruitment or differentiation of local Nestin(+) cells with potential stem cell character to angiogenic blood vessels may allow the definition of new therapeutic targets to reduce tumor resistance against anti-angiogenic drugs.